2015
DOI: 10.1007/s00330-015-4080-x
|View full text |Cite
|
Sign up to set email alerts
|

Low contrast media volume in pre-TAVI CT examinations

Abstract: PurposeTo evaluate image quality using reduced contrast media (CM) volume in pre-TAVI assessment.MethodsForty-seven consecutive patients referred for pre-TAVI examination were evaluated. Patients were divided into two groups: group 1 BMI < 28 kg/m2 (n = 29); and group 2 BMI > 28 kg/m2 (n = 18). Patients received a combined scan protocol: retrospective ECG-gated helical CTA of the aortic root (80kVp) followed by a high-pitch spiral CTA (group 1: 70 kV; group 2: 80 kVp) from aortic arch to femoral arteries. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 39 publications
3
36
1
Order By: Relevance
“…Therefore, there is a mismatch of pitch values between the two protocols (for example, 1.388 in the abdominal spiral scan in Group A vs. 0.813 in Group B). Likewise, although lower tube voltages are generally recommended [4,30], we could choose a minimum of 80 kV in automated tube voltage in Group A but not in Group B, as this would lead to a deactivation of tube current modulation in vHP3, even though this did not result in a statistically significant difference in mean kV. Furthermore, image noise as an image quality reference parameter for ATCM is set lower in vHP3 at 12.5 vs. 40 in vHP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a mismatch of pitch values between the two protocols (for example, 1.388 in the abdominal spiral scan in Group A vs. 0.813 in Group B). Likewise, although lower tube voltages are generally recommended [4,30], we could choose a minimum of 80 kV in automated tube voltage in Group A but not in Group B, as this would lead to a deactivation of tube current modulation in vHP3, even though this did not result in a statistically significant difference in mean kV. Furthermore, image noise as an image quality reference parameter for ATCM is set lower in vHP3 at 12.5 vs. 40 in vHP.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the CNR was consistently greater than 10 in the images of the aorto-femoral arteries, which exceeds the reported diagnostically acceptable CNR value. 13,24) For patients undergoing TAVI, renal dysfunction is reported as one of prognostic factors in the TAVI perioperative period. 10) Previously, several studies reported the importance of reducing the CM dose and subsequently reducing the risk of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…11,12) A previous study has reported success using low tube voltage techniques of second-generation dualsource CT (DSCT) system for TAVI planning. 13) But, low tube voltage imaging increased image noise unless tube current output was increased in previous reports. 14,15) Third-generation DSCT systems provide images with reduced noise, owing to substantially higher tube current output at low tube voltage than conventional DSCT systems.…”
mentioning
confidence: 92%
“…In contrast-enhanced CT, new-generation, dual-source CT and dedicated CT protocols offer sufficient imaging data with low dose of contrast media. [12][13][14] We used a second-generation, dual-source CT scanner ( Somatom Definition Flash, Siemens Healthcare, Forchheim, Germany) with low tube current and 100 kV, which were suggested by the automatic exposure control software CareDose 4D (Siemens Healthcare). Magnetic resonance angiography (MRA) has been reported to be equivalent to contrast-enhanced CT for the calculation of aortic annulus 15,16) but inferior for the assessment of aortic valve calcification and access root.…”
Section: Discussionmentioning
confidence: 99%